2017
DOI: 10.1149/08001.0313ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Molecular Dynamics of Dipole Layer Formation at High-k/SiO2Interface

Abstract: Origin of the electric dipole at high-k/SiO2 interfaces was investigated by classical molecular dynamics simulation. Both directions of the dipole are successfully reproduced with a simple two-body rigid ion model. The direction and magnitude of the dipole are determined by two opposing tendencies; oxygen ion migration from higher density oxide side to lower one, and the migration of metal cations in high-k toward SiO 2 side to form a silicate layer at the interface. The driving force of oxygen ion migration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The self-purging mechanism is the process by which HCO 3 À / CO 3 2À can be removed from the AEMFC under high current conditions, which may help to improvec ell performance, as demonstrated in several studies. [8,13,16,17,72] The process may be explained as follows:a tr elativelyh igh current densities, a large amount of OH À anionsa re formed asaresult of the high rate of ORR in the cathode [Eq. (7)].T he existing charge, which includes HCO 3 À and CO 3…”
Section: /Co 3 2à Concentration Through Self-purgingmentioning
confidence: 99%
See 4 more Smart Citations
“…The self-purging mechanism is the process by which HCO 3 À / CO 3 2À can be removed from the AEMFC under high current conditions, which may help to improvec ell performance, as demonstrated in several studies. [8,13,16,17,72] The process may be explained as follows:a tr elativelyh igh current densities, a large amount of OH À anionsa re formed asaresult of the high rate of ORR in the cathode [Eq. (7)].T he existing charge, which includes HCO 3 À and CO 3…”
Section: /Co 3 2à Concentration Through Self-purgingmentioning
confidence: 99%
“…In addition, CO 2 formation and release in the anode exhaust was showni ns everal experimental studies. [10,13,43,74] For example, by flowing the anode product stream through as olution of Ca(OH) 2 ,U nlu et al observed the formationo fam ilky precipitate (CaCO 3 )s econds after the start of fuel cell operation (by using O 2 + CO 2 in the cathode at av olume ratio of 1:2). [43] They showedt hat the amount of CaCO 3 precipitate increased with time as the cell operated.O ther works used analytical methods, such as IR spectroscopy, [69,72,75] MS, [13,74] and GC [10] to measuret he concentration of CO 2 in the anode exhaust gas of an AEMFC in operation.…”
Section: àmentioning
confidence: 99%
See 3 more Smart Citations